Open source software : implementation and management - Kavanagh, Paul (IEEE Computer Society Press technology series. Software development., 2004)
In 2004/5, over half of IT professionals will be looking at open source, most for the first time. This book provides key tools for System administrators, Network Administrators, IT project managers, and consultants who must evaluate and deploy open source software. This book details open source successes so far, explains which scenarios are the most realistic opportunities now, then gives the details needed to select these solutions, adopt the best tools and practices, introduce them to an organization, implement and manage them. The IT professional can use this book to review opportunities in their organization, evaluate components such as Apache, Linux, and OpenOffice against systems they know, and follow up in detail on their specific interests here and through referred resources. *Deployment scenarios categorized by function and industry *Rules of thumb on where and when open source software is or is not the right choice *Roadmaps for deployment in terms of the components of open source.